Porokeratosis ptychotropica of the scrotum: dermoscopic evaluation of an atypical presentation - Joana Cabete; Ana Fidalgo; André Lencastre; Filipa Diamantino; Alexandre João (Sociedade Brasileira de Dermatologia, 2015)
AbstractPorokeratosis ptychotropica is a rare variant of porokeratosis that is classically located on the gluteal and perianal regions, seldom extending to the genitalia. The authors report an atypical presentation of porokeratosis ptychotropica and discuss the use of dermoscopy in evaluating this dermatosis. Dermoscopic findings, although not specific to this variant of porokeratosis, are helpful in the differential diagnosis of other genital disorders. Histopathology, through the visualization of multiple cornoid lamellae, prevails as the gold standard for the definite diagnosis of porokeratosis ptychotropica.